Lubrication Performance of Engine Commercial Oils with Different Performance Levels: The Effect of Engine Synthetic Oil Aging on Piston Ring Tribology under Real Engine Conditions - Pantelis G. Nikolakopoulos; Stamatis Mavroudis; Anastasios Zavos (Lubricants, 2018)
To further improve efficiency in automotive engine systems, it is important to understand the generation of friction in its components. Accurate simulation and modeling of friction in machine components is, amongst other things, dependent on realistic lubricant rheology and lubricant properties, where especially the latter may change as the machine ages. Some results of research under laboratory conditions on the aging of engine commercial oils with different performance levels (mineral SAE 30, synthetic SAE10W-40, and bio-based) are presented in this paper. The key role of the action of pressure and temperature in engine oils’ aging is described. The paper includes the results of experiments over time in laboratory testing of a single cylinder motorbike. The aging of engine oil causes changes to its dynamic viscosity value. The aim of this work is to evaluate changes due to temperature and pressure in viscosity of engine oil over its lifetime and to perform uncertainty analysis of the measured values. The results are presented as the characteristics of viscosity and time in various temperatures and the shear rates/pressures. This paper also includes a Computational Fluid Dynamics (CFD) model, applying the experimental results in the piston ring tribology problem.